2013
DOI: 10.1007/s11249-013-0250-7
|View full text |Cite
|
Sign up to set email alerts
|

Wear, Plasticity, and Rehybridization in Tetrahedral Amorphous Carbon

Abstract: Wear in tetrahedral amorphous carbon (ta-C) and diamond is studied by molecular dynamics and near-edge x-ray absorption fine structure (NEXAFS) spectroscopy after self-mated sliding. Both theory and experiment observe the formation of a soft, mainly sp 2 hybridized amorphous carbon (a-C) tribolayer which grows faster for ta-C than for diamond surfaces sliding under otherwise similar conditions. The faster sp 3 → sp 2 transition in ta-C is explained by easy breaking of prestressed bonds in a nanoscale ta-C regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 45 publications
7
107
0
Order By: Relevance
“…Percentile values P95 for the absolute DFT values are given; these measure the range of data the GAP has to "learn". 75 and to ta-C, 76 and are faster than GAP by about a factor of 50.…”
Section: Structural Propertiesmentioning
confidence: 94%
“…Percentile values P95 for the absolute DFT values are given; these measure the range of data the GAP has to "learn". 75 and to ta-C, 76 and are faster than GAP by about a factor of 50.…”
Section: Structural Propertiesmentioning
confidence: 94%
“…Furthermore, the passivation of dangling bonds seems to play an important role [8]. The importance of the local sp3-sp2 transition and the corresponding formation of a soft amorphous layer were corroborated by a further study [9]. Furthermore, it was demonstrated that the polishing of a diamond crystal with a suspension of diamond particles depends on the formation of an amorphous layer and local sp3-sp2 transition [10].…”
Section: Introductionmentioning
confidence: 73%
“…Strong bonds between carbon atoms both within the amorphous layer and with the diamond substrate are causing high resistance forces, as shown by the red curves in Figure 11. According to Kunze et al [9], low friction of an amorphous carbon layer can only be expected if dangling bonds are passivated by ambient gases. Since such reactions were not considered in the present simulations, the friction forces remained high.…”
Section: Discussionmentioning
confidence: 99%
“…This ultra-low friction is thought to be generated by forming very thin and weak tribofilm at the mixed lubrication condition. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Martin et al proposed the possible mechanism of the super low friction was the forming water layer by the tribochemical reaction between ta-C and glycerol. [28][29][30][31][32][33] In this paper, the formation of water and acid was indicated as one possible chemical reaction for glycerol, as shown in (a) (a) (b) (b) For the oleic acid test, the water can be supplied from the ambient air.…”
Section: Resultsmentioning
confidence: 99%